Wat weet de Nederlander van de herkomst van Nederlandse woorden? [Was wissen Niederländer über die Herkunft niederländischer Wörter? What do Dutch speakers know about the etymology of Dutch words?] - van Bezooijen, Renée; Gooskens, Charlotte; Kürschner, Sebastian (Tijdschrift voor Nederlandse Taal- en Letterkunde, 2009)
There have been quite a few studies exploring popular ideas and knowledge of variation in the Dutch language area. However, emphasis has always been on the geographic dimension, historic variation remaining underexposed. In the present article we present the results of an investigation which focussed on the knowledge that non-linguists possess of the origin of high-frequent words in present-day spoken Dutch. We hypothesized that loans of English origin would be better recognized than loans from other languages because they are more recent and have been less adapted to the Dutch language. This hypothesis was confirmed. Although words of English origin constitute a relatively small portion of the high-frequent part of the lexicon of present-day spoken Dutch, they are far better recognized than words of German, French and Latin origin.
Keywords: Dutch; ethymology